Peeping through heart′s window: A case report of Fallots tetralogy - Bhowate R; Dubey A (Wolters Kluwer Medknow Publications, 2005)
Tetralogy of Fallot is a congenital heart defect. A combination of four abnormalities in heart allow oxygen rich and oxygen-depleted blood to mix. The resulting low-oxygen blood then circulates through the body. A child with the condition tends to develop slowly, eat poorly and grow slowly and may experience "blue" spells on crying and dyspnea on exertion. A 12 year old child with this congenital heart defect and cleft palate with cleft lip is discussed. Details of the latest diagnostic and treatment procedures are also presented.